Proposal of a convention between the program of modern languages of the ECCI university and the Shekinah Foundation (2015)
This project was consider the proposal of an agreement in the ECCI University and the Shekinah foundation, where each entity receives a benefit, due to the existence of the need to aid children from the foundation that take classes that permits them to learn a second language. On the other hand, the resources are limited to give a better quality and level of studies, also giving the opportunity of the ECCI University to provide social service.